Anthropometric parameters of elite male runners sprint: are body height and body weight predictors of results - Ratko Pavlovic; Ilona Mihajlović; Nikola Radulović; Siniša Nikolić (H.S. Skovoroda Kharkiv National Pedagogical University, 2022)
Purpose. Athletic sprint runs are cyclical movements of maximum intensity. Speed, reaction time, agility and explosiveness are of special importance in sprinters. The main goal of the research is to determine the influence of Body height (BH) and Body weight (BW) with the best achieved results of  in sprint disciplines (60m,100m,200m). Material and methods. In study included 40 competitors, top male sprinters (BH=180,45±6,88cm; BW=78,83±7,69kg). Their achieved best results in sprint disciplines were analyzed (60m, 100m, 200m). Pearson correlation coefficient was used to determine the relationship between body height and body weight and the results of sprint disciplines. Also a univariate model of regression analysis was applied and the relevant coefficients were calculated. The level of acceptance of statistical significance was set to p<0.05. Results. The simple regression analysis did not show a statistically significant influence of body height and body weight on the result of sprint running. Low correlations (BH vs. 100m = -0.306), (BW vs. 100m = -0.226) and (BH vs. 200m = -0.221) and insignificant correlations with an inverse relationship between results and anthropometric measures are mainly evident. Conclusion. Body height and body weight did not have a statistically significant effect on the results of the 60m sprint, while their influence is evident in the 100m, and especially in the 200m (but without statistical significance). This influence on the result of running 100 and 200m is a consequence of the exceptional motor-functional abilities of the sprinter to show greater force in the last phase of the rebound. Otherwise in the sprint, the rear rebound phase is much more important than the front rebound phase. A long step with the body weight (muscle) of the sprinter produces a higher rebound force, which with a big frequency of steps and good tecnique guarantees a good result.